The Highly Conserved Escherichia coli Transcription Factor YhaJ Regulates Aromatic Compound Degradation - Palevsky, Noa; Shemer, Benjamin; Connolly, James P. R.; Belkin, Shimshon (Frontiers in Microbiology, 2016)
The aromatic compound 2,4-dinitrotoluene (DNT), a common impurity in 2,4,6-trinitrotoluene (TNT) production, has been suggested as a tracer for the presence of TNT-based landmines due to its stability and high volatility. We have previously described an Escherichia coli bioreporter capable of detecting the presence of DNT vapors, harboring a fusion of the yqjF gene promoter, to a reporter element. However, the DNT metabolite, which is the direct inducer of yqjF, has not yet been identified, nor has the regulatory mechanism of the induction been clarified. We demonstrate here that the YhaJ protein, a member of the LysR type family, acts as a transcriptional regulator of yqjF activation, as well as of a panel of additional E. coli genes. This group of genes share a common sequence motif in their promoters, which is suggested here as a putative YhaJ-box. In addition, we have linked YhaJ to the regulation of quinol-like compound degradation in the cell, and identified yhaK as playing a role in the degradation of DNT.